Relationship between business strategy and human resource management practices in private and public limited companies in Malaysia - Yee, Koon Vui; Ali, Juhary (Journal of Business Management and Accounting, 2011)
This study examines the relationship between two business strategies (differentiation and low-cost) and six human resource management (HRM) practices (recruitment and selection, training and development, compensation, performance management, employment security, and work-life balance). Furthermore, an examination was conducted on the differences in such relationship between the Public and Private Limited companies in Malaysia. Structural equation modelling (SEM) was used to investigate the effect of business strategy on HRM practices and to determine the invariance effect of the two businesses ownership in the model. It is found that differentiation strategy stressed on all six HRM practices while low-cost strategy emphasized four HRM practices only. The results also show that the effects of business strategy and HRM practices performed in Public Limited companies are only slightly different from the ones performed in Private Limited companies.